x(2x-5)+x(2x-2)=(4x+3)(x-2)

Simple and best practice solution for x(2x-5)+x(2x-2)=(4x+3)(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(2x-5)+x(2x-2)=(4x+3)(x-2) equation:


Simplifying
x(2x + -5) + x(2x + -2) = (4x + 3)(x + -2)

Reorder the terms:
x(-5 + 2x) + x(2x + -2) = (4x + 3)(x + -2)
(-5 * x + 2x * x) + x(2x + -2) = (4x + 3)(x + -2)
(-5x + 2x2) + x(2x + -2) = (4x + 3)(x + -2)

Reorder the terms:
-5x + 2x2 + x(-2 + 2x) = (4x + 3)(x + -2)
-5x + 2x2 + (-2 * x + 2x * x) = (4x + 3)(x + -2)
-5x + 2x2 + (-2x + 2x2) = (4x + 3)(x + -2)

Reorder the terms:
-5x + -2x + 2x2 + 2x2 = (4x + 3)(x + -2)

Combine like terms: -5x + -2x = -7x
-7x + 2x2 + 2x2 = (4x + 3)(x + -2)

Combine like terms: 2x2 + 2x2 = 4x2
-7x + 4x2 = (4x + 3)(x + -2)

Reorder the terms:
-7x + 4x2 = (3 + 4x)(x + -2)

Reorder the terms:
-7x + 4x2 = (3 + 4x)(-2 + x)

Multiply (3 + 4x) * (-2 + x)
-7x + 4x2 = (3(-2 + x) + 4x * (-2 + x))
-7x + 4x2 = ((-2 * 3 + x * 3) + 4x * (-2 + x))
-7x + 4x2 = ((-6 + 3x) + 4x * (-2 + x))
-7x + 4x2 = (-6 + 3x + (-2 * 4x + x * 4x))
-7x + 4x2 = (-6 + 3x + (-8x + 4x2))

Combine like terms: 3x + -8x = -5x
-7x + 4x2 = (-6 + -5x + 4x2)

Add '-4x2' to each side of the equation.
-7x + 4x2 + -4x2 = -6 + -5x + 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-7x + 0 = -6 + -5x + 4x2 + -4x2
-7x = -6 + -5x + 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-7x = -6 + -5x + 0
-7x = -6 + -5x

Solving
-7x = -6 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-7x + 5x = -6 + -5x + 5x

Combine like terms: -7x + 5x = -2x
-2x = -6 + -5x + 5x

Combine like terms: -5x + 5x = 0
-2x = -6 + 0
-2x = -6

Divide each side by '-2'.
x = 3

Simplifying
x = 3

See similar equations:

| .40x+.15(140-x)=.25(140) | | 2/3(4+3) | | 6x^4+5x^2-6=0 | | 3/8=v+6 | | (3x+4)*(3x+4)=144 | | 2q+6=5(a-3) | | 8.5x-6.96=38.08 | | 2(8x-7)=2(3+8x) | | y+1/5=-3/4 | | -0.09p-0.04(6-4p)=0.03(p-4)-0.12 | | 17x-4x+27=4x-18 | | y-1/2=-7/8 | | 8r-4r+4=7r-r | | -2x-1=-8 | | 3x+4*3x+4=144 | | 5t+11(t-2)=5t+11(2t) | | (2x^2-5x+12)+(6x^2+8x-78)= | | w-6=-9 | | (8x+3)2=27 | | 1/2x^2-1/14-3/7=0 | | 2q+6=5 | | -5+u=-2 | | 0.16x+0.9(x-4)=0.01(2x-2) | | -y^2=-2y^2-6 | | 2x-11x=36 | | I=(2000)(3.7)(3.5) | | 1/12-9/16 | | x/4+1.2=-5.2 | | 12-3(2w+1)=10w-3(10+w) | | 7x/10+2=5x/6 | | 9w+2/2=2w+8/3+6 | | 5/X-2=4/7 |

Equations solver categories